The Working Musician's Handbook for Professional Success: How to Establish Your Value in the Real World - Hawkins, Kris (Rowman & Littlefield Publishers, 2022)
So, you’ve decided to become a professional musician—to turn your passion into a career. Now what? Unlike many professions, there is no clear-cut path to success in the music industry. Emmy-winning music producer, studio/session guitarist, and award-winning educator, Kris Hawkins explains some of the most basic and highly misunderstood concepts about what it takes to be a professional musician. Questions are answered like: “How do I find a gig?” “How much do I get paid?” “What is a copyright?” “What’s a PRO?” With over two decades of experience in the industry, Hawkins shares some of the insights that he has gained—successes as well as failures—in the hopes that you will learn from his missteps and triumphs. The Working Musician's Handbook for Professional Success focuses on real-life situations, including: Asserting your value Dealing with clients Protecting your work Treating your music as a business Financial management Finding work and networking There are many twists and turns within the music industry, and it can seem like a daunting task to try to understand it all. This handbook is your navigator and will help you develop a workable and effective strategy to start your career off on the right foot.